"Teacher competence and attitude as correlates of achievement in Yoruba language in Ibadan north-west local government area. " (2016)
"This paper explains that Yoruba language is a medium of instruction as stipulated by the National Policy on Education, at pre-primary and primary levels. Despite this importance as a language of instruction and a school subject, many factors militate against its effective teaching. Intervention by scholars, using many strategies has not yielded the needed improvement as poor performance in the subject persists. This paper therefore focused on teacher-related variables such as teacher competence and attitude. It also explains the relationship of these to achievement in Yoruba language. Three research questions were raised and three instruments (Achievement Test in Yoruba Language, r=0.78; Teacher Competence Scale, r=0.81; Teacher Attitude to Yoruba Language Questionnaire, r=0.89) were used to collect data. Two hundred and fifty (250) participants in five public senior secondary schools in Ibadan North-West Local Government were involved in the study. Data collected were analyzed using frequency count, Pearson Product Moment Correlation and multiple regressions. Findings revealed that there was a positive relationship between teacher competence in Yoruba and students' achievement (r=0.532, N=250, P<0.05). There was significant relationship between teacher attitude to Yoruba and students' achievement (r=0.711,N=250,P<0.05). Besides, there was 71% variation in the dependent variable as a result of the interaction of teachers' competence and attitude to Yoruba language. It is recommended that teachers of Yoruba language should master the subject, adopt effective teaching strategies and be organized while teaching the subject . "